Penerapan The 4 Discliplines of Execution (4DX) Pada Consumer Funding Unit Bank X - Nurul Izzatul Rahma; Sri Hartati Setyowarni; Winarto (Faculty of Social and Political Science, 2023)
This study aims to explain the implementation of four disciplines of execution in the consumer funding unit of Bank X. The four disciplines of execution are the discipline proposed by McChesney et al, 2012. This discipline is used by companies to help achieve company goals, namely increasing third-party funds. This study uses a qualitative research method with a case study approach. The research location used in this research is the consumer funding unit of Bank X. Triangulation is used to obtain the validity of the data. The result of this research is that after the consistent implementation of four disciplines of execution in 2021, the consumer funding Unit of Bank X managed to collect third-party funds of 725 billion from the specified target of 703 billion. For this reason, it was found that the increase in third-party funds was 103,13%. Thus, providing benefits such as increasing the target of increasing third-party funds from the previous year, reactivating the offline scoreboard, and carrying out other innovations in implementing the four disciplines of execution.